Examining experienced s&c coaches` reflections on the effectiveness of psychosocial behaviors in coaching - Szedlak, C.; Batey, J.; Smith, M. J.; Church, M. (International Journal of Coaching Science, 2020)
This study aimed to examine elite, experienced strength and conditioning (S&C) coaches` reflections on the effectiveness of psychosocial behaviors in S&C coaching. In particular, this study aimed to explore which psychosocial behaviors are essential, the process of how these might influence coaching practice, and how the development of psychosocial behaviors should be encouraged. Eight elite, experienced S&C coaches were recruited and partook in a semistructured interview. Using a reflexive thematic analysis, six themes were identified: understanding athlete`s needs, communicating effectively, caring and connecting with the athlete, practicing what you preach, the importance of reflective practice, and the contribution of formal training. The findings of this study enhance the literature by highlighting that elite, experienced S&C coaches perceive psychosocial behaviors to be essential in effective S&C coaching practice. In particular, the findings describe the processes of how identified psychosocial behaviors might positively influence athlete development by enhancing motivation, buy-in, and autonomy. In addition, the authors` results suggest that current S&C coach development programs are limited in facilitating the learning of psychosocial behaviors. Thus, their findings strengthen the call for S&C coach educators to utilize constructivist learning strategies including facilitated reflection to encourage the development of essential psychosocial behaviors that contribute to the holistic development of the athlete.